Development of an analytical model to predict the bending behavior of composite glulam beams in tension and compression. (January 2022) - Timbolmas, Cristian; Bravo, Rafael; Rescalvo, Francisco J.; Gallego, Antolino
Abstract: This research paper describes the mechanical results of an experimental test program and presents an analytical model that analyzes the relations between the global, tension and compresion moduli of elasticity of different layouts of composite glulam beams made with poplar wood in combination with pine wood and/or carbon fiber reinforced polymer (CFRP) subjected to bending. The experimental campaign was conducted employing acoustic non-destructive tests (NDT) as well as destructive mechanical ones (four-point bending tests). The aim is to evaluate the elastic global modulus and the moduli of timber in tension and compression along with the corresponding relations and consequent improvements for composite beams using the analytical model, based on the data from experimental tests. The analytical procedure entails two different approaches to estimate the timber behavior in tension and compression. The obtained analytical results of both approaches are subsequently compared for all of the beam layouts and experimental data, in which the maximum mean variation is up to 15%. In addition, the proposed analytical model is used in a parametric analysis that provides insights for the optimal design of a composite beam in terms of poplar wood percentage. Highlights: Analytical tensile, compresive and global relations for un/reinforced timber beams Improvement in moduli of elasticity of MoE due to combination of timber species or FRP Optima elastic moduli of composite timber beams due to combination timber species Accurate comparison non/destructive test on timber beams with analytical relations